Peran Wanita Karier Dalam Rumah Tangga Militer Berbasis Mubādalah - Dyah Erie (UIN Sunan Kalijaga Yogyakarta, 2025)
The dynamics of multiple roles are a common phenomenon in household relations, including in military families. The main issue addressed in this study concerns the challenges faced by women who are married to military personnel while also pursuing careers. These women face three concurrent roles: as wives, professionals in the public sector, and members of the Persit organization. Based on this context, two main research questions are formulated: first, how do career wives perform domestic, public, and social roles simultaneously? Second, how is the principle of Mubādalah reflected in husband-wife relations within the context of military households?. This study employs a field research method with a gender-based approach. Primary data were obtained through in-depth interviews with five military couples, conducted within the Group 2 PCBS Kopassus environment. The data were analyzed using the Miles and Huberman model, with analytical references to Caroline Moser’s Women’s Triple Role theory and the five pillars of Mubādalah. The findings show that career wives are able to carry out multiple roles proportionally with the support of their husbands. Husband-wife relationships are built on mutual reciprocity, as reflected in role-sharing, open communication, and emotional as well as spiritual support. The Mubādalah framework has proven to be a relevant approach in strengthening family resilience within military settings, leading to the formation of households that are harmonious, just, and equitable. This research contributes to the discourse on gender roles and family resilience in the context of modern military households. Dinamika peran ganda merupakan fenomena yang kerap muncul dalam relasi rumah tangga, termasuk dalam keluarga militer. Permasalahan utama yang diangkat dalam penelitian ini berkaitan dengan tantangan yang dihadapi oleh perempuan yang telah menikah dengan prajurit militer dan sekaligus menjalani peran sebagai wanita karier. Mereka dihadapkan pada tiga peran sekaligus, yaitu sebagai istri, profesional di sektor publik, dan anggota organisasi Persit. Berdasarkan kondisi tersebut, dirumuskan dua permasalahan utama, pertama bagaimana istri karier menjalankan peran domestik, publik, dan sosial secara simultan, kedua bagaimana prinsip Mubādalah dalam relasi suami istri diwujudkan dalam konteks rumah tangga militer. Jenis penelitian ini adalah penelitian lapangan dengan pendekatan gender. Data primer diperoleh dengan melakukan wawancara mendalam kepada lima pasangan dari rumah tangga militer. Dengan penelitian dilakukan di lingkup Grup 2 PCBS Kopassus. Data dianalisis dengan menggunakan metode Miles dan Huberman dengan merujuk pada teori Women’s Triple Role dari Caroline Moser serta konsep lima pilar Mubādalah. Hasil penelitian menunjukkan bahwa istri karier mampu menjalankan peran ganda secara proporsional dengan dukungan suami. Relasi suami istri dibangun dalam semangat kesalingan, ditunjukkan melalui pembagian peran, komunikasi terbuka, serta dukungan emosional dan spiritual. Konsep Mubādalah terbukti menjadi pendekatan yang relevan dalam memperkuat ketahanan keluarga militer, sehingga tercipta rumah tangga yang harmonis, adil, dan berkeadilan. Penelitian ini memberikan kontribusi bagi wacana gender dan ketahanan keluarga dalam konteks rumah tangga militer modern.